Monosaccharide derivatives as eco-friendly corrosion inhibitors for carbon steel in neutral and hydrochloric acid media - Rbaa M.; Lakhrissi L.; Lakhrissi Y.; Dohare P.; Lakhrissi B. (My University, 2025)
In this chapter, the authors present a synthesis of some works carried out within the framework of the study of the corrosion inhibiting activity of a set of monosaccharide derivatives as new biodegradable, nontoxic corrosion inhibitors, and respectful of the environment. The comparative study that they present reveals the existence of more than 20 compounds derivatives of monosaccharide used as corrosion inhibitors in neutral and acidic mediums, and which have given rise to very good corrosion inhibiting efficiencies. These studies of the corrosion inhibiting effect were studied using potentiodynamic polarization curves and electrochemical impedance spectroscopy methods. © 2020, IGI Global.